The great goddesses of Egypt - Lesko, Barbara S. (University of Oklahoma Press, 1999)
The book presents in depth histories of the cults of seven major goddesses and many excerpts from their literature--hymns, prayers, and magical spells as well as descriptions of ritual, temples and clergy.